(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Scleromyxedema is a rare condition which is clinically characterized by asymptomatic to itchy generalized papular and sclerodermoid eruption with histological findings which include mucin deposition and fibroblast proliferation. It can be associated with monoclonal gammopathy. Abnormalities in thyroid function must be ruled out in all cases where scleromyxedema is suspected. There have been several treatment options tried which includes chemotherapy, glucocorticoids, thalidomide, intravenous immunoglobulin and extracorporeal phototherapy. However, no satisfactory conclusion has been drawn. The case described represents scleromyxedema with absence of monoclonal spike or M peak. In our case, the patient showed significant clinical improvement in symptoms like movement of jaw, neck movement and improved mobility of upper and lower limbs within one month of treatment with prednisolone and thalidomide. There was also visible improvement in appearance of patient and papular lesions associated with scleromyxedema